The Representation of Masculinity in Cinema and on Television: An Analysis of Fictional Male Characters - Gürkan, Hasan (European Journal of Multidisciplinary Studies, 2022)
Mass media, especially cinema and television, are important devices that build and strengthen males and female roles in societies. The representation of gender in media is crucial because individuals get to know gender roles in the process of socialization. Besides the female identity, masculinity is also a constructible element and fictional male characters produced both in cinema and on television send messages about masculinity to the audience. In this study, the male representation both in the television series and in films were compared with this assumption and the question how male characters are represented on the two different mass media is examined in Turkey. Furthermore, the question "whether masculine representation reinforces the existing patriarchal male image or produces an alternative male model" is in the interest area of the study. The method of this study is reception analysis and in-depth interviews were undertaken with audiences with different demographic characteristics. As a result, it has been found that male representations in cinema and television are produced with similar myths, symbols, metaphors and messages, similar gender languages are used in different media, and fictional male characters in cinema and television have common characteristics.